Microbial d-xylonate production - Toivari, Mervi H. (Springer-Verlag, 2012)
d-Xylonic acid is a versatile platform chemical with reported applications as complexing agent or chelator, in dispersal of concrete, and as a precursor for compounds such as co-polyamides, polyesters, hydrogels and 1,2,4-butanetriol. With increasing glucose prices, d-xylonic acid may provide a cheap, non-food derived alternative for gluconic acid, which is widely used (about 80 kton/year) in pharmaceuticals, food products, solvents, adhesives, dyes, paints and polishes. Large-scale production has not been developed, reflecting the current limited market for d-xylonate. d-Xylonic acid occurs naturally, being formed in the first step of oxidative metabolism of d-xylose by some archaea and bacteria via the action of d-xylose or d-glucose dehydrogenases. High extracellular concentrations of d-xylonate have been reported for various bacteria, in particular Gluconobacter oxydans and Pseudomonas putida. High yields of d-xylonate from d-xylose make G. oxydans an attractive choice for biotechnical production. G. oxydans is able to produce d-xylonate directly from plant biomass hydrolysates, but rates and yields are reduced because of sensitivity to hydrolysate inhibitors. Recently, d-xylonate has been produced by the genetically modified bacterium Escherichia coli and yeast Saccharomyces cerevisiae and Kluyveromyces lactis. Expression of NAD(+)-dependent d-xylose dehydrogenase of Caulobacter crescentus in either E. coli or in a robust, hydrolysate-tolerant, industrial Saccharomyces cerevisiae strain has resulted in d-xylonate titres, which are comparable to those seen with G. oxydans, at a volumetric rate approximately 30 % of that observed with G. oxydans. With further development, genetically modified microbes may soon provide an alternative for production of d-xylonate at industrial scale.